Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 4: 1736-1737 - Gottsched, Johann Christoph (Briefwechsel, 2010)
The letters collected in Volume 4 show Gottsched at the height of his fame and recognition as a poetry theorist, linguist, philosopher, theater reformer, and publicist. Recurring themes in the correspondence, in addition to the introduction of German language instruction in high schools, are questions about poetry theory, the translation of foreign-language books, and the printing of works by Gottsched and his pen pals. The confrontation with representatives of Lutheran orthodoxy, of which the letters bear detailed witness, increasingly became a major problem for Gottsched, threatening his professional existence.